2023
DOI: 10.1002/adom.202202765
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure and Self‐Defect Evolution under Nonstoichiometric Effect Unlock Zero‐Thermal‐Quenching

Abstract: chip + yellow phosphors, (b) NUV LED chip + red-green-blue (RGB) phosphors. However, the former type features a low color rendering index (Ra) and residual rich blue light, which is not suitable to meet the increasingly prominent demand for human-centric health lighting. [2] NUVactivated w-LED shows a preponderance, for the acquisition of high-quality white light through the combination of different phosphors, meanwhile, the blue light can be minimized.In addition, during the working process, the Ohm effect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Based on the refinement result about the bond length of KSc 0.97 Cr 0.03 P 2 O 7 listed in Table S3 (ESI†), the distortion index of the [Sc/CrO 6 ] octahedron can be estimated to be 0.008, suggesting a highly symmetrical local coordinated environment. 35–37…”
Section: Resultsmentioning
confidence: 99%
“…Based on the refinement result about the bond length of KSc 0.97 Cr 0.03 P 2 O 7 listed in Table S3 (ESI†), the distortion index of the [Sc/CrO 6 ] octahedron can be estimated to be 0.008, suggesting a highly symmetrical local coordinated environment. 35–37…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained by assuming that at higher Δ the samples have a higher density of structural vacancies, resulting in a slight contraction of the lattice. 19 The formation of vacancies was further proven by 85 Rb magic angle spinning (MAS) nuclear magnetic resonance (NMR) characterization (Figure S18), which evidenced at least four different 85 Rb peaks in the range from 100 to −100 ppm. Considering that Rb + ions occupy two different locations (Rb 1 , Rb 2 ) in the tetragonal Rb 3 InCl 6 phase, 22 the NMR spectra indicated that the two types of Rb atoms could be surrounded by either 6 [InCl 6 ] 3− or 5 [InCl 6 ] 3− octahedra and 1 In vacancy, 32,33 which further splits the number of Rb sites to four, (Rb 1 , Rb 1-v ) and (Rb 2 , Rb 2-v ), resulting in 2*2 multiplets.…”
Section: ■ Introductionmentioning
confidence: 94%
“…Via efficient energy transfer from defects to Eu 2+ emitting centers, in the optimal sample (Δ = 0.1%), the PL intensity at 498 K corresponded to 114% of its initial value at room temperature. 19 The problem with metal oxides/nitrides is that their syntheses require high temperatures (>1500 K). 7 Metal halides, on the other hand, can profit from the much lower synthesis temperatures (some of them can even be prepared at room temperature) and, for some members of the class, the high photoluminescence quantum yield (PLQY).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] Compared with traditional light sources, phosphor-converted WLED (pc-WLED) technology has become the dominant light source because of its advantages of high efficiency, environmental protection, fast response time, and small volume. [10][11][12][13][14][15][16][17] Considering the application needs of various fields, there is still great room for the progress of pc-WLED technology. The color rendering index (CRI) is an important parameter to evaluate the quality of pc-WLEDs, and the higher the CRI, the better the color reproduction.…”
Section: Introductionmentioning
confidence: 99%